Elevated cerebrospinal fluid vasopressin in motor neuron disease. Issue 6 (June 1987) - Seckl, J R; Lightman, S L; Guiloff, R J
Abstract : CSF vasopressin levels were significantly elevated in eight patients with motor neuron disease (2.5 +/- 0.4 pmol/l) compared with controls (0.7 +/- 0.1 pmol/l). CSF oxytocin and plasma vasopressin concentrations were similar in the two groups. This finding may be a primary part of the disease process or an epiphenomenon related to increased autonomic and descending pathway activity secondary to abnormal function and/or loss of anterior horn cells.